Numerical Simulation of Two-roller Rotary Rolling Piercing of a New Heat-resistant Alloy SP2215 Seamless Pipe - Liang Kai, Yao Zhihao, Xie Xishan, Wang Hongying, Cheng Jian, Dai Weixing, Dong Jianxin (Teshugang)
In the process of rotary rolling and piercing for austenitic heat-resistant alloy， the improper selection of process parameters may result in phenomena such as coarse grain and mixed crystal in the pipe billet， or even fracture during processing， thereby impacting subsequent deformation and final product performance. Based on the previous thermaldeformation tests， this study established a material model for SP2215 alloy and utilized finite element software Simufact Forming 16.0 to simulate the rotary rolling and piercing of the alloy. The study analyzed dynamic changes in metal flow， strain field， stress field， strain rate field， temperature field， and rolling force during the skew rolling process. The simulation results are consistent with the actual deformation patterns. Furthermore， this study explored how process parameters such as head forward amount， roll speed， and initial temperature of billet affect both skew rolling performance and microstructure of the alloy. Ultimately an optimal rotary rolling and piercing process for the alloy is determined： head forward amount of 50 mm； roller spacing of 95.84 mm； guide plate spacing of 116.06 mm； roller speed at 50 r/min； and initial temperature range for tube billet at 1 100 ℃-1 150 ℃.